Conforming to career compromise: How a personal orientation can mitigate damages to organizational citizenship behavior - De Clercq, D.; Pereira, R. (Journal of Organizational Effectiveness: People and Performance, 2025)
Purpose: This investigation aims to unpack the negative connection between employees’ experience of resource-draining career compromise and their organizational citizenship behavior, by theorizing a mediating role of their depersonalization of organizational leaders and a moderating role of their conformity orientation in this connection. Design/methodology/approach: The hypotheses were tested with survey data collected among employees who operate in the construction retail industry in Portugal. Findings: A critical reason that frustrations about unwanted career adjustments translate into a reluctance to undertake work efforts that exceed formal job descriptions is that employees develop dehumanized perceptions of the people in charge of the company. This explanatory mechanism is less prominent, however, to the extent that employees’ personal orientation favors rule adherence. Practical implications: For HR managers, this research identifies a key channel, indifference to organizational leaders, through which disappointments about compromised career developments escalate into rejection of voluntary work activities, which otherwise might leave a positive impression on leaders and enhance employees’ careers. It also reveals that organizations can subdue this detrimental process by leveraging a sense of conformity among their workers. Originality/value: This study adds to HR management research by showing how a mismatch between employees’ current career situation and their own meaningful career goals paradoxically might direct them away from extra-role work behavior that otherwise could provide meaningfulness. This harmful dynamic, which can be explained by their propensity to treat organizational leaders as impersonal objects, can be avoided to the extent that employees draw from their conformity orientation.